URGENSI PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Solehudin, Much (Jurnal Teknologi dan Bisnis, 2022)
Education is an expensive investment that aims to prepare students to become good citizens who can give more to the state than to ask the state. This study tries to present a picture of the urgency of Islamic religious education in the digital age. The formulation of the problem in this research is how is the urgency of Islamic education in the digital age. This type of research is using literature study. In data collection techniques the author will explore the data in accordance with the discussion of the urgency of Islamic religious education. The results of the study: 1) Islamic Religious Education in the Digital Age has a very important role in facing global challenges, 2) Islamic religious education is not just explaining the theories of science of jurisprudence, aqeedah, and morality, but also how to explain these theories through multimedia, 3) The role of Islamic religion teachers is to fortify and direct students to be able to become a noble person, by giving examples and applying religious teachings well, 4) Islamic religious teachers invite students to think critically, 5) the role of Education The religion of Islam in the digital era does not mean to prohibit using internet media or means that support learning today but rather to prevent it.